2019
DOI: 10.1177/1471301219827709
|View full text |Cite
|
Sign up to set email alerts
|

“If it helps someone, then I want to do it”: Perspectives of persons living with dementia on research registry participation

Abstract: Registries are an important platform to which persons with dementia and other cognitive impairments can contribute to research studies. Registries also provide an opportunity for patients to stay informed about current studies. Engaging patients in registry development can increase sustainability of a registry and patient retention in clinical registries. We sought the perspective of persons with dementia and their accompanying family members about their registry participation experiences, barriers and facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In all dyads, either the CG or the PLWD expressed an interest in educating themselves. Our findings are similar to another qualitative study that found that the personal benefit of education was one of the motivators for PLWD to enroll in a research registry (Lee et al, 2019). While the parent study described in this article had a core component of providing education to both the intervention and control group, we do recognize that not all clinical trials would incorporate education into their protocol.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In all dyads, either the CG or the PLWD expressed an interest in educating themselves. Our findings are similar to another qualitative study that found that the personal benefit of education was one of the motivators for PLWD to enroll in a research registry (Lee et al, 2019). While the parent study described in this article had a core component of providing education to both the intervention and control group, we do recognize that not all clinical trials would incorporate education into their protocol.…”
Section: Discussionsupporting
confidence: 90%
“…We found participants enrolled in the trial because they wanted to support another person. Altruism has been found to be related to enrollment in clinical trials in other research works (Bardach et al, 2018;Cox, et al, 2019;Lee et al, 2019). For example, in a survey of 87 individuals enrolled in one dementia clinical trial, the majority of participants rated the potential to help themselves or a loved one and to help others in the future, as important factors that affected their decision to enroll in the trial; few respondents reported participating to make others happy (Bardach et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work leverages data systems employed to capture patient data in the PROMPT registry, demonstrating another use of clinical patient registries for meaningful patient engagement and service improvement. Previous work has shown that neurological and psychiatric patient populations do not see registry participation as burdensome but as an altruistic way to contribute to research that may or may not also provide personal benefit (Lee et al, 2019). Enhancing communication and preparation for clinic appointments has been shown to improve health outcomes in non-pandemic times (Entwistle & Watt, 2006;Street et al, 2009), and we can reasonably extrapolate that this would be true during times of social and physical distancing as experienced during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 77%
“…This work leverages data systems employed to capture patient data in the PROMPT registry, demonstrating another use of clinical patient registries for meaningful patient engagement and service improvement. Previous work has shown that neurological and psychiatric patient populations do not see registry participation as burdensome, but as an altruistic way to contribute to research that may or may not also provide personal benefit (Lee et al, 2019). Enhancing communication and preparation for clinic appointments has been shown to improve health outcomes in non-pandemic times (Entwisthle & Watt, 2006; Street et al, 2009) and we can reasonably extrapolate that this would be true during times of social and physical distancing, as experienced during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%